2009
DOI: 10.1186/1757-1626-2-7487
|View full text |Cite
|
Sign up to set email alerts
|

Standardized natural product cannabis in pain management and observations at a Canadian compassion society: a case report

Abstract: An adult Caucasian male with excruciating pains following multiple traumas was monitored, daily, over one year while managing chronic pain by self-administering quantifiable amounts of natural cannabis. Tetrahydrocannabinol, Cannabidiol, and Cannabinol were all measured in tinctures, capsules, smoke-able product plus some baked goods, prior to their administration. By allowing standardization, the subject was able to develop a daily regimen of pain management that was resistant to a battery of most patent anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 1 publication
1
11
0
Order By: Relevance
“…Induction of apoptosis by cannabinoids in prostate and colon cancer cells may be phosphatase dependent [14]. Our case studies confirmed cannabinoid (CB) efficacy in reducing muscle spasticity in multiple sclerosis [15], pain levels over a 12-month period [16] and Cannabis responsive head injury induced multiple disabilities [17].…”
Section: Introductionsupporting
confidence: 68%
“…Induction of apoptosis by cannabinoids in prostate and colon cancer cells may be phosphatase dependent [14]. Our case studies confirmed cannabinoid (CB) efficacy in reducing muscle spasticity in multiple sclerosis [15], pain levels over a 12-month period [16] and Cannabis responsive head injury induced multiple disabilities [17].…”
Section: Introductionsupporting
confidence: 68%
“…An earlier publication on the effects of standardized cannabis and chronic pain management describes a similar tolerant response [2]. A phenomenon often witnessed at the Society is persons with Celtic genealogy require 3 -5 five times greater dosage than those of Middle European or other descent.…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, Indica's tend to have higher levels of Cannabidiol (CBD), a cannabinoid with demonstrated powerful antiinflammatory action (26). Our studies using HPLC to quantify cannabinoid concentrations in standardized capsules finds that a ratio roughly 1:10 CBD:THC, works well for pain relief in an oral preparation at doses of 20 to 100 mg (depending on tolerance) THC, every four to six hours (21,22).…”
Section: Strain Specificitymentioning
confidence: 97%
“…A very special thanks to John Berfelo who's courage in treating his chronic pain with cannabis inspired and lent to our first case study (21) and much of the research referred to in this text.…”
Section: Acknowledgementsmentioning
confidence: 99%
See 1 more Smart Citation